Oral administration of a potential mast cell stabilizer, tHGA, prevents IgE-mediated anaphylaxis in rats - Tan, Ji Wei; Daud, Ahmad Israf; Shaari, Khozirah; Tham, Chau Ling (2016)
The prevalence of allergic diseases, such as asthma and anaphylaxis, has increased dramatically over the past decades. The critical role of mast cells in allergy makes them attractive candidates for targeting allergic diseases. Mast cell stabilizing drugs are used clinically to prevent allergic reaction to common allergens by inhibiting the release of allergic mediators from mast cells. Despite the relative success as disodium cromoglycate for the treatment of allergic diseases including bronchial asthma, allergic conjunctivitis and vernal keratoconjunctivitis, there still remains an urgent need for the discovery of the next generation of mast cell stabilizing drugs that are less expensive and require less frequent dosing schedules. In the regard, recent developments have included studies on substances isolated from natural sources or newley synthesized compounds. 2, 4, 6, -trihydroxy-3-geranylacetophenone (tHGA) is an active compound originally found in a local shrub known as Melicope ptelefolia. Our previous studies demonstrated that tHGA was able to dosedependetly inhibit morphological changes as well as the syntheses of pre-formed and newly synthesized mediators such as histamine, leukotriene C4 (LTC4), and interleukin-4 (IL-4) in celullar model of mast cell activation. Activated mast cell release mediators that can induce life treathing anaphylaxis through crosslinking of immunoglobuin (lg) E and aggregation of the antigen receptor for igE (FciuRI) on mast cells. This current study aims to investigate the effect of a potential mast cell stabilizer, tHGA, on igE-mediated passive systemic anaphylaxis in Sprague Dawley rats. DNP-igE-sensitized rats were orally administered with tHGA (20, 40 and 80mg/kg) one hour before challenged with DNP-bovine serum albumin (DNP-BSA) to induce anaplylaxis. One hour after challenge, the rats were sacrificed and the sera and peritoneal mast cell (PMCs) were collected. The level of key mediators including histamine, LTC4, and IL-4 were eximined. The morphology of PMCs was also analysed by using light and electron microscopy. The results showed that pretreatment with tHGA retained the normal morphology of PMCs with minimal release of their granules’ content which further resulted in a significant reduction on the level of key mediators in the sera (p< 0.05). as a conclusion, this current study demonstrated that tHGA, as a potential mast cell stabilizer, was able to exert its therapeutic effects on animal model of passive systemic anaphylaxis through inhibition of mast cell activation.